Die Auloden in der griechischen Musikkultur = The Aulodes in the musical culture of ancient Greece - Scheithauer, Andrea (Archiv für Musikwissenschaft, 2024)
Due to the utterly scant transmission of written sources, we are only able to glean a rudimentary impression of the singers and how these performers went about their professional careers. By and large, information about these musicians corresponds to the knowledge we have of other proponents of the arts, and yet the development of their specialization, attested to as early as the sixth century B.C., is singular among musicians at that time. Although aulody was included in the arena of artistic tournaments for several centuries, it did not play a central role in Greek musical life and eventually disappeared from competitions due to its lack of popularity.
Gesehen am 30.07.2025